2022
DOI: 10.23736/s2724-5276.20.05725-4
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation for immunocompromised children with acute respiratory distress syndrome: a French referral center cohort

Abstract: Background: Immunocompromised children are likely to develop a refractory acute respiratory distress syndrome (ARDS). The usefulness of providing extracorporeal life support (ECLS) to these patients is a subject of debate. The aim of our study was to report the outcomes and to compare factors associated with mortality between immunocompromised and non-immunocompromised children supported with veno-venous ECMO. Methods:We performed a retrospective monocentric study in the French pediatric ECMO center of Armand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…As an example, children suffering from malignancies (solid tumor, leukemia, or hematopoietic cell transplantation [HCT]) are a specific population for whom the decision to use ECMO remain challenging. Recent observational study reported wide survival rate mainly depending on the underlying disease (13, 33). To help physician to evaluate the potential benefit of ECMO in immunocompromised patients, Di Nardo et al (34) published experts recommendation on ECMO used in HCT and Zinter et al (35) proposed a decision-making graph to better define potential candidate for ECMO in the HCT children population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, children suffering from malignancies (solid tumor, leukemia, or hematopoietic cell transplantation [HCT]) are a specific population for whom the decision to use ECMO remain challenging. Recent observational study reported wide survival rate mainly depending on the underlying disease (13, 33). To help physician to evaluate the potential benefit of ECMO in immunocompromised patients, Di Nardo et al (34) published experts recommendation on ECMO used in HCT and Zinter et al (35) proposed a decision-making graph to better define potential candidate for ECMO in the HCT children population.…”
Section: Resultsmentioning
confidence: 99%
“…T he 2015 Pediatric Acute Lung Injury Consensus Conference (PALICC) international recommendations on pediatric acute respiratory distress syndrome (PARDS) published 11 recommendations regarding the role of extracorporeal membrane oxygenation (ECMO) support in PARDS (1). Since 2015, there have been advances in ECMO research in adults with acute respiratory distress syndrome (ARDS) (2)(3)(4)(5)(6), devices and cannulas (7), management (8)(9)(10), and expanding indications, most notably COVID-19 (11)(12)(13).…”
mentioning
confidence: 99%
“…Immunocompromised and non-immunocompromised children up to 18 years old with ARDS were evaluated in a French study with 111 participants [ 37 ]. The survival rate at 6 months after the intensive care discharge was significantly lower in immunocompromised patients compared to non-immunocompromised ones (41.7% vs. 62.8%; p = 0.04).…”
Section: Long-term Outcomes In Childrenmentioning
confidence: 99%